2020
DOI: 10.1039/d0dt01982h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-NIR absorption spectroscopy study of the formation of ternary plutonyl(vi) carbonate complexes

Abstract: We present the first experimental evidence for the ternary complexation of calcium and magnesium ions with plutonyl(VI) tricarbonate species in carbonate-containing aqueous solutions using visible-NIR spectrophotometric titration. Prior to studying...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Only one spectroscopic study of the Pu( vi )-oxalate system has been reported, 20 so additional guidance for understanding changes in our systems was obtained from previous reports on the spectral impact of changing Pu( vi ) coordination. 39–45…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one spectroscopic study of the Pu( vi )-oxalate system has been reported, 20 so additional guidance for understanding changes in our systems was obtained from previous reports on the spectral impact of changing Pu( vi ) coordination. 39–45…”
Section: Discussionmentioning
confidence: 99%
“…Only one spectroscopic study of the Pu(VI)-oxalate system has been reported, 20 so additional guidance for understanding changes in our systems was obtained from previous reports on the spectral impact of changing Pu(VI) coordination. [39][40][41][42][43][44][45] The peaks at 839 and 846 nm were determined to represent Pu(VI)-oxalate complexes that shared the pentagonal bipyramidal coordination environment of the fully hydrated Pu(VI)-aquo ion ([PuO 2 (H 2 O) 6 ] 2+ ). 47 The strong peaks in the 830-850 nm region were lost as the f-f transition became Laporte forbidden with the addition of an inversion center (i.e., hexagonal bipyramidal coordination).…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%